A European multicentre drug utilisation study of the impact of regulatory measures on prescribing of codeine for pain in children. Issue 8 (20th June 2019) - Hedenmalm, Karin; Blake, Kevin; Donegan, Katherine; Macia, Miguel‐Angel; Gil, Miguel; Williams, Julie; Montero, Dolores; Candore, Gianmario; Morales, Daniel; Kurz, Xavier; Arlett, Peter
Abstract: Purpose: In June 2013, following recommendations from the World Health Organization (WHO) and Food and Drug Administration (FDA), the European Medicines Agency agreed updates to the codeine product information regarding use for pain in children younger than 12 years and children undergoing tonsillectomy or adenoidectomy (TA) for obstructive sleep apnoea. This study was conducted to (a) assess effectiveness of these measures on codeine prescribing in the "real‐world" setting and (b) test feasibility of a study using a common protocol by regulators with access to databases. Methods: The study was performed using BIFAP (Spain), CPRD (UK), and IMS® Disease Analyzer (France and Germany) databases. Prescribers included general practitioners (GPs) (France and UK), GPs and paediatricians together (Spain), and GPs, paediatricians, and ear, nose, and throat (ENT) specialists separately (Germany). Between January 2010 and June 2015, prevalence of codeine prescribing was obtained every 6 months, and a time series analysis (joinpoint) was performed. Codeine prescribing within ±30 days of TA was also identified. Furthermore, doses, durations, and prior prescribing of other analgesics were investigated. Results: Over the 5‐year period, codeine prescribing decreased in children younger than 12 years (by 84% in France and Spain, 44% in GP practices in Germany, and 33% in the United Kingdom). The temporal pattern was compatible with the regulatory intervention in France and the United Kingdom, whereas a decrease throughout the study period was seen in Germany and Spain. Decreased prescribing associated with TA was suggested in ENT practices in Germany. Conclusions: Codeine prescribing for children decreased in line with introduced regulatory measures. Multidatabase studies assessing impact of measures by EU regulators are feasible.